Spatiotemporal Up-Regulation of Mu Opioid Receptor 1 in Striatum of Mouse Model of Huntington’s Disease Differentially Affecting Caudal and Striosomal Regions - Morigaki, Ryoma; Lee, Jannifer H.; Yoshida, Tomoko; Wüthrich, Christian; Hu, Dan; Crittenden, Jill R.; Friedman, Alexander; Kubota, Yasuo; Graybiel, Ann M. (Frontiers in Neuroanatomy, 2020)
The striatum of humans and other mammals is divided into macroscopic compartments made up of a labyrinthine striosome compartment embedded in a much large surrounding matrix compartment. Anatomical and snRNA-Seq studies of the Huntington’s disease (HD) postmortem striatum suggest preferential decline of some striosomal markers, and mRNAs studies of HD model mice concur. Here, by immunohistochemical methods, we examined the distribution of the canonical striosomal marker, mu opioid receptor 1 (MOR1), in the striatum of the Q175 knock-in mouse model of HD in a postnatal time series extending from 3 to 19 months. We demonstrate that, contrary to loss of many markers for striosomes, there is a pronounced up-regulation of MOR1 in these Q175 knock-in mice. We show that in heterozygous Q175 knock-in model mice ( 192 CAG repeats), this MOR1 up-regulation progressed with advancing age and disease progression, and was particularly remarkable at caudal levels of the striatum. Given the known importance of MOR1 in basal ganglia signaling, our findings, though in mouse, should offer clues to the pathogenesis of psychiatric features, especially depression, reinforcement sensitivity, and involuntary movements in HD.